Pupils' opinions on motor activities in early school education - Eligiusz Madejski; Magdalena Majer; Jacek Szalewski; Roger Madejski (University of Applied Sciences in Tarnow, Poland, 2018)
Introduction: Lower grades students participate in Physical Education lessons mainly for pleasure, as well as for emotional and utilitarian reasons. For many students at this educational stage their attendance in Physical Education classes is the only form of participation in organized physical activity. Therefore, motor activities should provide children with the opportunity for experiences of different kind and motivate them to physical activity. The aim of the research was to find out what are the opinions of early school students on physical activities. Material and methods: The research covered 256 students at the age of 7-10, 128 girls and 128 boys. The method of open categorized interview was applied to collect the empirical material. Results: The results of the survey have shown that the vast majority of children expressed their positive opinions on their participation in physical activities. The students enjoyed team games and various exercises most. Nearly 9% of the examined were dissatisfied with the lack of discipline during the lesson and not observing fair play principles by their classmates during exercises. The said dissatisfaction increased with age. The examined did not show much interest in swimming classes, and the 9-10 age group showed no interest in them at all. Conclusions: The large majority of students, irrespective of their age, are willing to participate in motor activities.